Comparison of the Impact of Functional Communication-Based and Theory of Mind-Based Intervention Programs on Distress Tolerance in Children with Autism Spectrum Disorder - Beigi , Rezvan; Fakhri , Mohammad Kazem; Haydari, Shaban (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to compare the impact of functional communication-based intervention training and theory of mind-based training on distress tolerance in children with autism spectrum disorder (ASD) in Shahin Shahr, Isfahan. This research is applied in terms of its objective and semi-experimental with a pre-test and post-test design in terms of methodology. The statistical population included all children with ASD in Shahin Shahr during the 2023–2024 academic year. From a sample of 120 individuals, 45 children with ASD were selected using G*Power software calculations, inclusion and exclusion criteria, and a purposive non-random sampling method. Data collection methods consisted of library research and field study. The instrument used for data collection in this study was the Distress Tolerance Questionnaire. Participants received interventions involving functional communication training and applied behavior analysis, and post-tests were administered to both groups. Hypotheses were tested using SPSS software to analyze the questionnaire data. The findings indicate that the effectiveness of functional communication-based intervention training and theory of mind-based training on distress tolerance in children with ASD in Shahin Shahr, Isfahan, differs significantly.